The effect of temperature and storage time on the migration of antimony from polyethylene terephthalate (PET) into commercial bottled water in Kuwait - Allafi, Ahmad R (Acta Biomedica Atenei Parmensis, 2020)
Polyethylene terephthalate (PET) is a safe material used widely in manufacturing plastic water bottles. However, recent studies have linked PET with Antimony which poses both acute and chronic health effects. The objective of this study was to investigate the effect of storage and temperature on the amount of antimony leached to the bottled water. Three brands of bottled water were used for this analysis. Samples were stored at 25oC for three months to examine the storage duration on antimony levels. To examine the effect of temperature on antimony levels, samples were stored at -5oC, 25oC and 50oC for 24 hours, respectively. To investigate the duel effect of both temperature and time on antimony levels, samples from one brand were heated at 50 oC for 7 days. Antimony analysis was conducted using a Thermo Electron Element 2 single-collector double-focusing magnetic sector inductively coupled plasma mass spectrometer (ICP-MS). Results showed that there were no statistical differences of antimony concentrations before and after storage at room temperature. Heating samples to 50 oC increased the antimony concentrations to 8.530 ppb and 16.8 ppb in 24 hours and 7 days, respectively. Although the range of Antimony concentrations in the bottled waters is well below WHO maximum contaminant level if stored at room temperature, inappropriate and prolonged storage of plastic bottles may lead to exceed the maximum contaminant level of 6 ppb. The data collected from this study can be useful to plastic bottle manufacturers for setting a safe storage temperature for PET bottles.